PENUNDAAN PELAKSANAAN PEMILIHAN KEPALA DAERAH SERENTAK MENURUT SISTEM KETATANEGARAAN - Siti Afiyah; Rusydi Rusydi; Rizky Dwi Chorniawan (Universitas Islam Darul Ulum, 2021)
This research is based on the government's steps in the midst of the current COVID-19 pandemic and with the simultaneous 2020 Regional Head Elections being held initially on 23 September 2020 and postponed to December 2020. The Simultaneous Regional Head Election is a Regional head elections are carried out directly by people who meet the requirements, which are carried out simultaneously in regions in Indonesia. The 2020 simultaneous elections is the fourth batch of simultaneous elections conducted for regional heads as a result of the December 2015 election. There are 270 regions that carry out Simultaneous Pilkada 2020, the details are 9 provinces, 224 regencies, and 37 cities.